Results of anterior cruciate ligament restoration using «all inside» techniques - Golovakha, Maksim; Krasnoperov, Sergiy; Titarchuk, Rostyslav; Zabielin, Ivan; Tverdovsky, Anatoliy; Orljanski, Weniamin (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
In spite of the new technology, the number of unsatisfactory results of anterior cruciate ligament reparation is not to be reduced. Improving of techniques goes by two directions: decreasing of surgical traumatization and improving the anatomical position of transplant. Objective: to evaluate the effectiveness of recovery by anterior cruciate ligament «all inside». Methods: results of anterior cruciate ligament restoring «all inside» in 346 patients (201 men, 145 women) operated in the period 2013–2015 analyzed. Average age: 20 years — 75 patients, 21– 30 — 116, 31–40 — 101, over 40 — 54. Drilling tool RetroDrill made channels or FlipCutter were used, fixation in the femur and tibia using system TightRope or equivalent. Results: the recurrence of instability appeared in 3 patients, 2 cases — stable reactive synovitis. Pain at the site of the implants and their removal was not observed. Performance on a scale IKDC were: A-162, B-34, C-15, D-3. The main advantages of the method include a significant reduction in pain (VAS score on 1–3 on the 2nd day); rapid r ecovery o f range of motion; no hematomas at the site exit channel tibia bone; employment of a single tendon only 92 % of cases, preservation of function m. gracilis, absence of implant in bones channels, which is important when you perform revision surgery. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA;">Conclusions:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> the method of anterior cruciate ligament reparation using technology «all inside» with fixing system type TightRope is the similar to other technologies and provides positive results in patients with anterior instability of the knee joint.